2013
DOI: 10.5539/elt.v6n4p97
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian Gifted Students’ Use of English Language Learning Strategies

Abstract: Many studies have been done on language learning strategies employed by different type of learners and in various contexts. However, very little studies have been done on gifted students regarding language learning. Gifted students have unique characteristics and have different ways if thinking and learning. These characteristics affect how they learn a language. The main objective of the study was to investigate language learning strategies use among gifted students enrolled in special programme called PERMAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
2
11
0
1
Order By: Relevance
“…The students stated that they could observe improvements consistently once they applied certain strategies in language learning. This result corresponded with a study conducted by Yunus et al (2013) who indicated that the proficient Malaysian secondary schools students were high strategy users.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The students stated that they could observe improvements consistently once they applied certain strategies in language learning. This result corresponded with a study conducted by Yunus et al (2013) who indicated that the proficient Malaysian secondary schools students were high strategy users.…”
Section: Discussionsupporting
confidence: 66%
“…In other words, perception as well as belief is strongly correlated with an individual's cognitive ability to evaluate and make sense of knowledge (Thornton, 2009). The review of literature has illustrated that local researchers in Malaysia direct more attention on the relationship between language learning strategies and learners' characteristics such as gender (Razak et al, 2012, Yunus, Sulaiman & Embi, 2013, Subramaniam & Palanisamy, 2014, English language proficiency (Yunus et al, 2013), year of study (Subramaniam & Palanisamy, 2014) and motivation (Teh et al, 2009). Hence, perspectives of learners toward language learning strategies have received insufficient attention and there is a need to bridge this literature gap.…”
mentioning
confidence: 99%
“…From the study, the learners preferred social and cognitive strategies compared to other strategies. According to Yunus, Sulaiman and Embi (2013), learning strategies are vital in second language acquisition and investigation on the learning strategies used by the learners provides an insight to the processes involved in language learning such as cognitive, social and affective processes.…”
Section: Resultsmentioning
confidence: 99%
“…또한 성취수준이 뛰어난 영재학생들의 경우 다양한 학습 전략을 활용하는 것으로 보고된 바 있어 (김유미, 류성림, 2010;Zimmerman & Martinez-Pons, 1990) (양수민, 이귀숙, 2012;DeCharms, 1984;Leondari & Gialamas, 2002;Schunk, 1983;Shen & Pedulla, 2000;Vallerand et al, 1994;Zimmerman, Bandura, & Martinez-Pons, 1992 (구영수, 양연숙, 2013;문병상, 2000;조현철, 유수창, 2011;Cho & Ahn, 2003;Vandestoep, Pintrich, & Fagerlin, 1996;Yunus, Sulaiman, & Embi, 2013;Zimmerman & Martinez-Pons, 1990)을 뒷받침해 준다.…”
Section: 선행연구 고찰unclassified